Determinants of Asset Management Effectiveness and Its Impact on The Fairness of The Asset Presentation - syaifudin, mohamad; ritchi, hamzah; avianti, ilya (Universitas Pendidikan Indonesia, 2020)
This study aims to analyze asset management effectiveness and its impact on the fairness of the presentation of assets in the local government balance sheet. This research was conducted in 2019 with respondents who were the goods management apparatus at local government organizations in 27 local government in West Java Province. A total of 172 questionnaires were distributed and filled out by the goods management apparatus using the google form application. This research method uses quantitative methods with multiple linear regression equation models with the help of SPSS software. The results of this study indicate the effectiveness of the performance of asset management can be influenced by the commitment of the leadership, the competence of goods management employees, internal control, application of regional asset management information systems. The performance of regional asset management also has an impact on the fairness of the presentation of assets on the local government balance sheet.